2021
DOI: 10.3389/fphys.2021.649604
|View full text |Cite
|
Sign up to set email alerts
|

Chronic E-Cigarette Aerosol Inhalation Alters the Immune State of the Lungs and Increases ACE2 Expression, Raising Concern for Altered Response and Susceptibility to SARS-CoV-2

Abstract: Conventional smoking is known to both increase susceptibility to infection and drive inflammation within the lungs. Recently, smokers have been found to be at higher risk of developing severe forms of coronavirus disease 2019 (COVID-19). E-cigarette aerosol inhalation (vaping) has been associated with several inflammatory lung disorders, including the recent e-cigarette or vaping product use-associated lung injury (EVALI) epidemic, and recent studies have suggested that vaping alters host susceptibility to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 88 publications
3
16
2
Order By: Relevance
“…Indeed, single cell RNA sequencing studies estimated that only 1% to 6% of cells express ACE2 in the respiratory tract, principally in airway epithelial cells, type II pneumocytes, and nasal goblet cells ( 13 , 36 , 37 ). A large meta-analysis demonstrated an increase in the expression of ACE2 and the entry factor protease TMPRSS2 with age, in men, and with smoking ( 38 ), which correlated with findings in mice showing increased ACE2 expression with age and exposure to cigarette smoke and vaping ( 39 , 40 ). Because infection is confined largely to the airway and not lung parenchyma, the hACE2 KI mouse could provide a model of self-limited infection, mild COVID-19 disease, and possibly transmission.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, single cell RNA sequencing studies estimated that only 1% to 6% of cells express ACE2 in the respiratory tract, principally in airway epithelial cells, type II pneumocytes, and nasal goblet cells ( 13 , 36 , 37 ). A large meta-analysis demonstrated an increase in the expression of ACE2 and the entry factor protease TMPRSS2 with age, in men, and with smoking ( 38 ), which correlated with findings in mice showing increased ACE2 expression with age and exposure to cigarette smoke and vaping ( 39 , 40 ). Because infection is confined largely to the airway and not lung parenchyma, the hACE2 KI mouse could provide a model of self-limited infection, mild COVID-19 disease, and possibly transmission.…”
Section: Discussionsupporting
confidence: 52%
“…Elevated ACE2 activities were found in the bronchial-lavage fluid from EC users and smokers [20]. Full body exposures to “Mint” but not “Mango” aerosols generated from JUUL™ pods increased ACE2 levels in mouse lung [30]. Three additional lung studies found elevated ACE2 levels following treatment with aerosols containing a mixture of PG (propylene glycol)/VG (vegetable glycerol) and nicotine [31,32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Masso-Silva et al on experimental animals revealed that e-cigarette aerosols led to changes in the lung gene expression and neutrophil activation. This was also observed with the intake of vaping mint, as the ACE-2 expression increased in animal models [61].…”
Section: Disease Pathology In E-cigarettes and Covid-19mentioning
confidence: 53%